PENYELENGGARAAN PELAYANAN TERPADU SATU PINTU PADA DINAS PERIJINAN KOTA DENPASAR - Agus Indra Febriyana, I Putu; Anom Pemayun, Cok Istri (Kertha Negara : Journal Ilmu Hukum, 2013)
Simplification of licensing procedures through the establishment of the Department of Licensing is an effort that is expected to accommodate the needs of the community as an institution truly One Stop Service, where various types of licenses that are still there are many scattered in so on education, in 105 types of licenses, all taken care of in one door, which is at the Department of Licensing, Denpasar Government policy in the simplification of licensing with the Parallel System raises the issue how integrated one-stop service delivery in order to improve public services in the Department of Licensing Denpasar, and Is that a benchmark in order to achieve an integrated service delivery doors are good at Denpasar Licensing Agency. This method is a kind of empirical research. It can be concluded from the factors improving services through two procedures with the Front Office and Back Office so you can easily and quickly take care of the permit. And communities in applying for a license must match the application requirements Denpasar owned by the Department of Licensing that the lack of barriers and obstacles in the implementation of One Stop Services and can run well.
Keywords: Licensing, Factors, Servants